2015
DOI: 10.1371/journal.pone.0119485
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance and Clinical Characterization of Influenza in a University Cohort in Singapore

Abstract: BackgroundSoutheast Asia is a potential locus for the emergence of novel influenza strains. However, information on influenza within the region is limited.ObjectivesThis study was to determine the proportion of influenza-like illness (ILI) caused by influenza A and B viruses in a university cohort in Singapore, identify important distinctive clinical features of influenza infection and potential factors associated with influenza infection compared with other causes of ILI.MethodologyA surveillance study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Among students and staff at the National University of Singapore presenting with ILI, 21.1% had laboratory‐confirmed influenza in 2007 and 32.8% in 2007‐09. Although the study conducted in 2007‐09 detected a higher influenza‐positivity rate, the proportion of influenza B was lower comparing to the study in 2007 (6.7% vs 16.1%) as influenza A/H1N1pdm09 became the predominant type in the second half of the 2007‐09 study …”
Section: Resultsmentioning
confidence: 61%
“…Among students and staff at the National University of Singapore presenting with ILI, 21.1% had laboratory‐confirmed influenza in 2007 and 32.8% in 2007‐09. Although the study conducted in 2007‐09 detected a higher influenza‐positivity rate, the proportion of influenza B was lower comparing to the study in 2007 (6.7% vs 16.1%) as influenza A/H1N1pdm09 became the predominant type in the second half of the 2007‐09 study …”
Section: Resultsmentioning
confidence: 61%
“…Influenza infection was confirmed by PCR. Details of this cohort have been described previously [14]. …”
Section: Methodsmentioning
confidence: 99%
“…Recruitment via mass advertisements has also been found to underrepresent important populations who are at high risk of ILI and influenza, such as children and the elderly [ 14 ]. Recent virological studies have demonstrated that targeted disease surveillance, which is based on specific populations such as university students and military recruits, is not only cost-effective but also complementary to existing systems [ 16 , 17 ]. However, the effectiveness of internet-based surveillance systems using targeted samples has not been thoroughly explored.…”
Section: Introductionmentioning
confidence: 99%